Relationship Separation and Help-seeking: Reporting on an Agency Study. Issue 3 (3rd July 2019) - Howard, Robin; Dunk-West, Priscilla; Natalier, Kristin
ABSTRACT: Relationship separation affects many Australians with around 20, 000 divorces involving children formalised per year. For profit, government and nongovernment organisations all offer services for separated couples and families. Despite promotion of specialist services such as mediation and child-centred services, which seek to assist families to navigate what is a complex interaction between public and legislative structures, there is little known about the potentially broader array of supports and information people use following separation. Better understanding of help-seeking behaviours for separating couples enables more effective targeted policy and service delivery. Individuals with children accessing a nongovernment-funded program for support during separation ( n  = 134) were asked to complete a survey that was designed to track their help-seeking behaviour. We found that help-seeking for legal services was more common than seeking help for self-care, but that both were important for many people in the sample. Friendship networks, and medical and health professionals were the most common sources of information and support. We argue that social work has a role in promoting and supporting parents who are separating to access a broader range of informal support networks and professional services. IMPLICATIONS: Parental separation and divorce can involve complex legal, emotional, and social issues. Friendship networks as well as professional services are important sources of support. Social workers should be aware of their role in helping separating parents access support. Social work education should provide theoretical and skills-based knowledge to equip social workers to work with people experiencing separation.